Comparison With David as a Means of Evaluating Character in the Book of Kings - Amos Frisch (Journal of Hebrew Scriptures, 2011)
Comparison with David is a literary device employed throughout the book of Kings as a way to assess the kings whose deeds are recounted in the book (both kings of Judah and at least Jehu of Israel). Explicit comparisons to David are linked to literary allusions to him and understood as a single basic phenomenon. The comparisons also include a sophisticated system of inverted analogies (among David, Solomon and Jeroboam).